Wage Inequality and the Effort Incentive Effects of Technological Progress - Campbell Leith; Chol-Won Li (Center for Economic Studies and ifo Institute (CESifo), 2001)
To explain the rise in the college wage premium in developed economies in the past decades, the present paper examines the effects of technological progress on workers effort incentives, which determine the effective labor supply. Five effort incentive effects of technological progress are identified, and through these we obtain a number of results. Firstly, we establish that wage inequality can increase following an acceleration in skill-neutral technological progress. Secondly, an increase in skill-biased technological progress means, (i) skilled wages overshoot, (ii) unskilled wages undershoot, and hence (iii) wage inequality overshoots their respective long-run values. Thirdly, endogenising the number of skilled and unskilled workers on the basis of economic incentives does not eliminate wage inequality even in the long run. Fourthly, we can obtain hysteresis effects in the determination of long-run wage inequality. Finally, government policies which raise the equilibrium rate of unemployment are likely to reduce the impact of technical progress on inequality, and this may help to explain the relative increase in inequality in the US and UK compared with other European economies. Our focus on the supply-side complements studies which emphasize the impact of skill-biased technological progress on relative demand for skill workers.
Keywords: 330